The Impact of Corruption on Healthcare Services: Empirical Evidence from the MENA Region - Salah Alnahdi (International Journal of Economics and Financial Issues, 2020)
The aim of this article is to analyse the perceived effect of corruption on health for a sample of 15 MENA countries over the period 1996-2018. This study used an econometric approach and a system of simultaneous equations models (SEMs) to explore relationships among latent variables and to examine the direct and indirect effects of corruption on health. Results showed that corruption affect negatively health care services and hinders economic growth for the MENA region. Furthermore, we found a bi-directional causal relationships between economic growth and health, and as well as between corruption and economic growth.  However, the results support the occurrence of unidirectional causality between corruption and health. These empirical insights are of particular interest to policymakers as they help identify areas that are sensitive to corruption in health sector and the palliative strategies to be put in place.